Social Reflections Of Greenhouse Gass Emission Mitigations In Livestock Sector In Indonesia - Tati Herawati (Indonesian Center for Animal Research and Development, 2012)
Greenhouse gas affect on the global warming and climate change has been realized recently. The livestock contribution on the emission of greenhouse gases to the atmosphere has the social and economic impact not only to the livestock holder but also to the surrounding society. Various mitigation technology actually have available both through the selection type feed low emissions as well as awarding supplemen, the addition of chemicals or mechanical means in the process of manufacture of fodder that can decrease methane production.The awareness of livestock raiser at small scale level to utilize available resources locally, would help mitigation activity and received economically beneficial returns in the forms of biogas and organic fertilizer. Revenues generated from the installation of biogas Rp. 600.000/month when converted to LPG price and value in calories (Liquefied Petroleum Gas) and B/C ratio of 1.35. Means that investments are economically viable. The present condition indicates that wider socialization to farmers on the relationship between livestock and the global warming and climate change. The need in order to grab social and economic benefit from utilizing local resources. Key words: Social, economic, global warming, greenhouse gas